NEW RECORDS OF THREE SPECIES OF HORSE FLIES (DIPTERA:TABANIDAE) IN IRAQ WITH REMARKS ON SOME ECOLOGICAL ASPECTS . - Alaa N.H. Ali; Dhia K. Karim (Basrah Journal of Veterinary Research)
The research includes superficial taxonomic study of the horse fly family Tabanidae in the Province of Basrah / South of Iraq , according to the seven districts of the province , There are Al-Mdainah , Al-Qurnah , Shatt Alarab, Abu Al-Khasib, Al-Zubair , Al-Fao and Basrah center . The Results of the study were showed recording three species for the first time in Iraq back to the three genera , and were Haematopota subcylindrica , Atylotus agricola and Hybomitra peculiaris .